The Inverted Initiation Rituals in Shakespeare with a Special Emphasis on Hamlet - Wicher, Andrzej (Multicultural Shakespeare: Translation, Appropriation and Performance, 2021)
The article deals the possibility of applying Vladimir Propp’s, basically anthropological idea of “the inverted ritual” to the interpretation of certain plays by William Shakespeare, particularly Hamlet. The said inversion concerns three rituals: the sacrificial ritual, where the passive and obedient victim suddenly rebels, or at least becomes difficult to control (which is the case, for example, of Ophelia in Hamlet); of the initiatory ritual, where the apparently benevolent master of the characters initiation is shown as a monster (which can be exemplified by Claudius, Hamlet’s uncle); and of the matrimonial ritual, where the theoretically loving husband (more rarely wife), or lover, is revealed as a highly malicious and unpredictable creature, an example of which can be Hamlet himself. The article makes use of the work of such critics as G.K. Wilson, Harold Bloom, Vladimir Propp, René Girard, and Mircea Eliade.